Model Pengembangan Multikultural Berbasis Psikologi Pendidikan di Sekolah Dasar : Studi Sistematis Perkembangan Sosial-Emosional Siswa - Mohammad Rizal Roikhan; Asmawati (Yayasan Al-Afif, 2025)
The aim of this study is to investigate the development of multicultural education based on educational psychology in elementary schools. The method used is a systematic literature review based on secondary data, which is systematically designed to identify, elicit, and synthesize research related to the development of multicultural education in elementary schools based on the principles of educational psychology. Secondary data sources are taken from various leading academic databases such as Google Scholar, ScienceDirect, ERIC (Education Resources Information Center), and Garuda (Research and Academic Document Gallery). Each article found is described using a study quality assessment scheme based on the criteria of methodological validity, topic relevance, generalizability, and the level of novelty of the findings. The results of this study indicate that the principles of educational psychology in the social-emotional development of elementary school students emphasize the importance of a supportive, inclusive, and needs-based learning environment. With a holistic approach that integrates cognitive, emotional, and psychomotor aspects, and respects the pace and learning style of each child, education can shape individuals who are intelligent, confident, empathetic, and capable of positive interactions. Teachers act as facilitators, drawing on Ki Hajar Dewantara's philosophy, to create enjoyable and meaningful learning, enabling children to grow holistically in terms of their intellect, heart, and identity. This research makes a significant contribution to the development of educational science and child psychology, particularly in integrating a multicultural approach with an educational psychology framework at the elementary school level.